(untitled) - Mathis, Robert L. (Minneapolis, 1994)
This book research and an effective blend of solid theory and contemporary practice highlight emerging trends driving change in HRM today, including technology, globalization, and HR metrics. Trust the authoritative resource for human resource management to offer the most current look at HR and its impact on today's organizations
Keywords: Personnel management,Quản trị nhân sự